Introducing the Historical Varieties of Democracy dataset: Political institutions in the long 19th century. (May 2019) - Knutsen, Carl Henrik; Teorell, Jan; Wig, Tore; Cornell, Agnes; Gerring, John; Gjerløw, Haakon; Skaaning, Svend-Erik; Ziblatt, Daniel; Marquardt, Kyle L; Pemstein, Daniel; Seim, Brigitte
The Historical Varieties of Democracy dataset (Historical V-Dem) contains about 260 indicators, both factual and evaluative, describing various aspects of political regimes and state institutions. The dataset covers 91 polities globally – including most large, sovereign states, as well as some semi-sovereign entities and large colonies – from 1789 to 1920 for many cases. The majority of the indicators come from the Varieties of Democracy dataset, which covers 1900 to the present – together these two datasets cover the bulk of 'modern history'. Historical V-Dem also includes several new indicators, covering features that are pertinent for 19th-century polities. We describe the data, coding process, and different strategies employed in Historical V-Dem to cope with issues of reliability and validity and ensure intertemporal and cross-country comparability. To illustrate the potential uses of the dataset we describe patterns of democratization in the 'long 19th century'. Finally, we investigate how interstate war relates to subsequent democratization.